Training the disadvantaged youth and labour market outcomes: Evidence from a randomized controlled trial in Bangladesh - Das, Narayan Chandra (BRAC Research and Evaluation Division, 2022)
This paper estimates the effects of a youth training program in Bangladesh on labour market outcomes. The program provides on-the-job and classroom training to the disadvantaged and unemployed youth. On-the-job training is provided through apprenticeship under a local master craftsperson. Classroom training curriculum includes theoretical training on specific trades as well as soft-skills training. The program is implemented by BRAC, the largest NGO in the world. BRAC’s Research and Evaluation Division (BRAC-RED) conducted a Randomized Controlled Trial on the 2016 cohort of the program. A baseline survey was conducted in June 2016 covering 3,186 youths. In June-July 2017 a follow-up survey was conducted, successfully reaching 2,946 youths. Using the data generated by BRAC RED, I show that on-the-job training increases labour market participation of the program participants by 22.6 percentage points (59%), total time devoted to earning activities by 59%, and earnings by 44%. It increases both self- and wage-employment. The effect on employment is found to be larger for females. Additional effects of classroom training over on-the-job training on overall employment and earnings are small in magnitude. Results, however, indicate that if classroom training is added to on-the-job training, the effects shift from self- to wage employment. Results also show that employment in firms where the apprenticeship took place is a channel for the effect on wage employment. The benefit-cost ratio for on-the-job training is estimated to be 6.34, demonstrating high returns on the investment made under this initiative. It is also shown that the scale at which the program was implemented, employment effects for beneficiaries were not achieved through the displacement of non-beneficiaries.